Studi Sosiolinguistik pada Nadhoman Terjemah Kitab Syu’abul Iman Karya KH. A Wahab Muhsin - Basajan, abdul rahman (Prodi Pendidikan Bahasa dan Sastra Daerah, 2024)
Sociolinguistic studies are part of modern linguistic studies which cover all linguistic phenomena and their communities. This study can explain word preferences or language structures that differentiate one literary work from another based on the relationship between individuals, populations, periodization and people's lifestyle patterns. The source of sociolingistics research is all types of communication that use language, both spoken and written in all varieties of languages ​​in the world. This research aims to describe sociolinguistic relationships and traces of their application in Nadhoman's